2019
DOI: 10.1002/cpt.1564
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Drug‐Drug Interaction Study Assessing a Novel Drug Transporter Phenotyping Cocktail With Adefovir, Sitagliptin, Metformin, Pitavastatin, and Digoxin

Abstract: A new probe drug cocktail containing substrates of important drug transporters was tested for mutual interactions in a clinical trial. The cocktail consisted of (predominant transporter; primary phenotyping metric): 10 mg adefovirdipivoxil (OAT1; renal clearance (CL R )), 100 mg sitagliptin (OAT3; CL R ), 500 mg metformin (several renal transporters; CL R ), 2 mg pitavastatin (OATP1B1; clearance/F), and 0.5 mg digoxin (intestinal P-gp, renal P-gp, and OATP4C1; peak plasma concentration (C max ) and CL R ). Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
1
22
0
1
Order By: Relevance
“…In this evaluation based on a detailed characterization of digoxin pharmacokinetics in healthy volunteers, ABCB1 SNP combinations had a significant albeit small influence on the (apparent) bioavailability but not on the renal elimination of the drug. This result is in line with a previous non-compartmental analysis (NCA) of one of the studies included in this population pharmacokinetic evaluation, where C max and AUC 0–24 h of digoxin were significantly higher in CGC/CGT and TTT/TTT, but not in CGC/TTT carriers, compared to CGC/CGC 52 . In contrast, in a study by Xu et al subjects carrying TTT/TTT showed a higher average C max and AUC 0–4h 31 compared to CGC/CGC in a Chinese Han population, but the observed difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this evaluation based on a detailed characterization of digoxin pharmacokinetics in healthy volunteers, ABCB1 SNP combinations had a significant albeit small influence on the (apparent) bioavailability but not on the renal elimination of the drug. This result is in line with a previous non-compartmental analysis (NCA) of one of the studies included in this population pharmacokinetic evaluation, where C max and AUC 0–24 h of digoxin were significantly higher in CGC/CGT and TTT/TTT, but not in CGC/TTT carriers, compared to CGC/CGC 52 . In contrast, in a study by Xu et al subjects carrying TTT/TTT showed a higher average C max and AUC 0–4h 31 compared to CGC/CGC in a Chinese Han population, but the observed difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…However, we cannot rule out that our limited sample size was insufficient to detect minor differences in renal clearance between groups. Also, in our previous NCA analysis, no significant difference in renal clearance was found between CGC/CGC and other SNP combination groups 52 . When digoxin was given intravenously or orally with a strong P-gp inducer, renal elimination of digoxin was not relevantly affected, but the AUC 0–144 h for both administration routes and AUC 0–3 h , C max , and bioavailability for oral administration were decreased.…”
Section: Discussionmentioning
confidence: 69%
“…Dosing several probe drugs in a cocktail is a way to assess the DDI risk of multiple transporters simultaneously in the same subject. 41,42 However, equivalence of the pharmacokinetic parameters of probe drugs between single dose and simultaneous dosing as a cocktail would need to be validated prior to its use. 42 Leveraging of multiplexed endogenous biomarkers is one possible way to facilitate simultaneous DDI assessment across multiple drug transporters early in clinical development without the potential need for DDI studies with individual probes or probe drug cocktails.…”
Section: Articlementioning
confidence: 99%
“…In this regard, as previously described for OATP1B, it is envisioned that physiologically-based pharmacokinetic (PBPK) model-based analysis will aid the design of clinical studies. 41 A PBPK model for metformin has already been constructed and it is able to describe the metformin-cimetidine DDI involving MATE1 inhibition. 43 Likewise, the construction of PBPK models for 1-NMN and m 1 A will advance the prediction of OCT2 and MATE1/2-Kmediated DDI in drug development.…”
Section: Articlementioning
confidence: 99%
“…The five substrates showed no interactions among each other, as the PK profiles from discrete or cocktail dosing were comparable. Clinical DDI studies with cocktail substrates reduce the number of clinical trials, speed up drug development processes and enable better ethical compliance (Trueck et al, ). Similar cocktail approaches have been reported in human with micro‐dosing and in cynomolgus monkeys for both major CYPs and transporters (Kosa et al, ; Prueksaritanont et al, ).…”
Section: Transporter‐mediated Ddimentioning
confidence: 99%